First measurement of sub-GeV [nu][subscript mu] charged-current coherent pion production on the argon nucleus in MicroBooNE - Hussain, Adil (My University, 2026)
I present a measurement of the [nu][subscript mu] charged-current (CC) coherent pion production cross section on the argon nucleus, performed using data collected by the MicroBooNE liquid argon time projection chamber (LArTPC) exposed to the Booster Neutrino Beam (BNB) at Fermilab. The analysis utilizes the full MicroBooNE dataset corresponding to an exposure of 1.31 x 10²¹ protons on target (POT), with a mean neutrino energy of approximately 0.8 GeV... See PDF for full text of abstract.
Keywords: Neutrino; Cross-section; MicroBooNE; Charged-current coherent pion production; GENIE neutrino generator; LArSoft